1980
DOI: 10.1128/aac.17.6.908
|View full text |Cite|
|
Sign up to set email alerts
|

Combined antibacterial activity of amoxicillin with clavulanic acid against ampicillin-resistant strains

Abstract: Strains of bacteria resistant to beta-lactam antibiotics have been increasing in number and are becoming troublesome in clinical medicine. The in vitro antibacterial activity of amoxicillin combined with clavulanic acid was determined on selected ampicillin-resistant clinical isolates. Synergistic effects were produced by amoxicillin with clavulanic acid against ampicillin-resistant strains of Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Proteus vulgaris, and Bacteroides f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…Clavulanic acid, a naturally occurring 3-lactamase inhibitor, may prevent the inactivation of these P-lactams (8,21). Combinations of clavulanic acid and amoxicillin are significantly more active both in vitro and in vivo against certain ,B-lactamase-producing bacteria than is amoxicillin alone (11,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clavulanic acid, a naturally occurring 3-lactamase inhibitor, may prevent the inactivation of these P-lactams (8,21). Combinations of clavulanic acid and amoxicillin are significantly more active both in vitro and in vivo against certain ,B-lactamase-producing bacteria than is amoxicillin alone (11,18).…”
mentioning
confidence: 99%
“…Clavulanic acid, a naturally occurring 3-lactamase inhibitor, may prevent the inactivation of these P-lactams (8,21). Combinations of clavulanic acid and amoxicillin are significantly more active both in vitro and in vivo against certain ,B-lactamase-producing bacteria than is amoxicillin alone (11,18).The purposes of this study were: (i) to determine the efficacy and safety of the combination of amoxicillin and potassium clavulanate in the treatment of urinary tract infections; (ii) to attempt to relate therapeutic responses to the results of antibody-coated bacteria tests (25) …”
mentioning
confidence: 99%
“…A very potent 3-lactamase inhibitor is clavulanic acid, a fermentation product of Streptomyces clavuligerus (14,15). Although its intrinsic antibacterial activity is comparatively weak, it irreversibly inhibits a wide range of ,B-lactamases of Richmond types II through V (12), protecting the P-lactam antibiotics administered simultaneously (e.g., amoxicillin from inactivation) and rendering the lactamase-producing organisms susceptible to the action of the antibiotic (8,18). A new formulation of amoxicillin plus clavulanic acid (4:1 by weight) exploits this strongly synergistic effect by combining the two components for oral application (see [1,7,13]).…”
mentioning
confidence: 99%
“…Previous studies have shown that clavulanic acid not only irreversibly inactivates beta-lac-tamase but also exhibits synergism with amoxicillin against amoxicillin-resistant bacteria. 7,8,18,19 The rate of amoxicillin resistance in Saudi Arabia is markedly higher than those reported in the United States and Europe. 20,21 In this study we found that these same clinical strains of E. coli, Klebsiella pneumoniae, Proteus organisms, and staphylococci showed increased susceptibility to Augmentin as compared to ampicillin.…”
Section: Discussionmentioning
confidence: 53%